The Influence of Capital Intensity, Political Cost, and Financial Distress on Tax Avoidance in Coal Mining Companies in Indonesia 2014-2020 - Ari Minarwan; Teti Haryati (Budapest International Research and Critics University, 2022)
This study aims to determine the effect of capital intensity, political cost, and financial distress on tax avoidance in companies listed on the Indonesia Stock Exchange. This study uses a samples of mining companies in the mining coal sector who listed on the IDX during the 2014-2020 period. The data in this research are secondary data obtained fromwww.idx.co.id, datacollection techniques using purposive sampling method, then processed in Eviews 10. In analyzing the data, the researcher conducts descriptive statistics techniques, classical assumption tests, multiple linear regression, and hypothesis testing. Based on the results of hypothesis testing, it was found that capital intensity has negative influence on tax avoidance, political cost has no influence on tax avoidance, and financial distress has positive influence on tax avoidance.